Pengaruh Promosi, Harga, dan Tempat Terhadap Keputusan Pembelian Produk Pertanian di UD Aneka Tani Kecamatan Arut Selatan Kabupaten Kotawaringin Barat - Shofiyah Shofiyah; Hartini Hartini (Anterior Jurnal, 2018)
The success of marketing a product, especially agricultural production facilities involves various factors such as promotion, price, and location of sales. Consumer purchase decision in UD. Aneka Tani cannot be separated from the influence of each factor. To find out whether or not these factors affect sales, then conducted research at UD. Aneka Tani method of data collection is done by accidental sampling method. The results of this study indicate that Promotion (X1), price (X2), and place (X3) partially do not give effect to purchasing decision in UD shop. Aneka Tani. From the result of data analysis indicate that t count value of each independent variable is under t table 2.056. Hence the alternative hypothesis (Ha) is rejected and the null hypothesis (Ho) is accepted, meaning partially does not affect the independent variable of promotion (X1), price (X2), and place (X3) to the dependent variable of purchase decision (Y). Promotion (X1), price (X2), and place (X3) simultaneously do not give effect to purchase decision at UD store. Aneka Tani. Where Fcount (2,533) < F table (2.96).